Trends in Cartilage Repair Techniques for Chondral Defects in the Hip in Germany: An Epidemiological Analysis from 2006 to 2022 - Sebastian Frischholz; Tizian Heinz; Manuel Weißenberger; Sebastian Philipp von Hertzberg-Boelch; Philip Anderson; Martin Lüdemann; Axel Jakuscheit; Maximilian Rudert; Ioannis Stratos (Life)
Cartilage repair techniques for chondral defects in the hip are crucial for treating conditions like femoroacetabular impingement, developmental dysplasia, and osteonecrosis, especially in young patients to delay the progression of osteoarthritis. This study aims to present age and sex distributions and trends in hip-preserving surgeries in Germany from 2006 to 2022, analyzing 116,179 procedures using the German OPS coding system. The procedures were categorized into three groups: debridement, refixation, and regeneration. Arthroscopy was more common than arthrotomy (98,916 vs. 17,263). Males underwent more procedures than females (63,771 vs. 52,408). Debridement had a monomodal age distribution peaking at 43.42 years, while refixation and regeneration exhibited bimodal patterns. Regenerative procedures were primarily performed on younger patients (average 27.73 years). A Joinpoint analysis showed an initial increase in procedures, peaking around 2013, followed by a decline. Arthroscopic procedures peaked at approximately 9000 in 2013, whereas arthrotomies peaked at around 1200 after 2014. The decline in procedures post-2013 may reflect refined surgical indications and a shift towards outpatient settings. These findings underscore the trend towards minimally invasive, scaffold-based treatments, with regenerative techniques showing promising outcomes in younger patients. Future research should focus on prospective comparative studies and cost–benefit analyses to guide clinical decision-making.